Herding Behavior between Rating Agencies - Alexander Rieber; Steffen Schechinger (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We investigate whether credit rating agencies systematically follow each other's rating decisions. Therefore we rely on the rotation of rating analysts within credit rating agencies and their impact on the rating. Using this institutional setup we can disentangle causal herding behavior from simple co-movement between credit rating agencies due to changes in firm fundamentals. Rating analysts have substantial influence on ratings and we use their individual optimism/pessimism as instrumental variable to estimate causal effects of a rating change induced by an analyst on rating changes by other credit rating agencies. For our comprehensive sample of U.S. and European firms, rated by S&P, Moody's and Fitch between 1995 - 2016, we find significant herding behavior among credit rating agencies. This average herding behavior amounts to 0.4 notches for a one notch change at another credit rating agency, which is roughly half the size of the simple co-movement between credit rating agencies.
Keywords: G14; 330